Who the Hell Are You?: Gender Performativity in Tom Stoppard's Hapgood - Ayyildiz, Nilay Erdem (Univ Ljubljana, 2023)
Tom Stoppard is an outstanding playwright, embellishing his plays with scientific and philosophical approaches and presenting complicated, mysterious plots to the reader. He bases the plot of his postmodern play, Hapgood (1988), on quantum theory and draws an analogy between Werner Heisenberg's principle of indeterminism, termed The Uncertainty Principle, and international espionage. Thus, he constructs the complicated relationship between the particle and the whole throughout the play to depict the relativistic and deceptive relationship between sex and gender. Focusing on the title character of the play, the present study proposes that the play represents the fluid and indeterminate nature of gender and identity within the context of espionage and indeterminism. Hapgood, who is a mother, a lover and a successful master agent in a man-dominated British secret service, navigates between masculinity and femininity during a day. Moreover, she metamorphoses into her twin, who is entirely different from her, except for their identical faces, to entrap the mole in the office. The study consults Judith Butler's theory of gender performativity and fluidity to indicate the unpredictable and uncertain nature of 'gender identity', which formulates itself through performances in social relations and trespasses the heterosexual matrix. It juxtaposes the Butlerian approach with the Uncertainty Principle in quantum theory pertaining to the confusing relationship between gender, the body and identity. The Butlerian analysis of the play reveals that particularly the modern way of life makes women transgress the Cartesian dichotomies of sex/gender, masculine/ feminine and man/woman through the fluidity of their roles even during a single day and makes it difficult to find out who is really who.
Kdo za vraga si ti? Spolna performativnost v igri Hapgood Toma Stopparda
Keywords: gender; Hapgood; identity; norms; performativity; quantum